2018
DOI: 10.3389/fmicb.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Stress-Activated Degradation of Mitochondrial Respiratory Complexes in Yeast

Abstract: Repair and removal of damaged mitochondria is a key process for eukaryotic cell homeostasis. Here we investigate in the yeast model how different protein complexes of the mitochondrial electron transport chain are subject to specific degradation upon high respiration load and organelle damage. We find that the turnover of subunits of the electron transport complex I equivalent and complex III is preferentially stimulated upon high respiration rates. Particular mitochondrial proteases, but not mitophagy, are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In addition, several studies have reported that mitophagy promotes the elimination of ROS through the removal of damaged mitochondria [ 9 , 10 , 13 , 47 ]. Elevated respiration rates stimulate mitophagy degradation of the complex I equivalent and complex III of mtETC [ 27 ]. Therefore, the complex I equivalent and complex III are key mediators of ethanol stress related changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have reported that mitophagy promotes the elimination of ROS through the removal of damaged mitochondria [ 9 , 10 , 13 , 47 ]. Elevated respiration rates stimulate mitophagy degradation of the complex I equivalent and complex III of mtETC [ 27 ]. Therefore, the complex I equivalent and complex III are key mediators of ethanol stress related changes.…”
Section: Resultsmentioning
confidence: 99%
“…has reported that H 2 O 2 in the mitochondrial matrix has a signaling role in ethanol tolerance by Yap1p [ 5 ]. Additional studies indicate that mild ROS, as a signal molecule, regulates mitophagy [ 10 - 12 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The K + -ionophore valinomycin induces overproduction of mitochondrial ROS and subsequent mitochondrial damage in yeast (Andrukhiv, Costa, West, & Garlid, 2006; Selivanov et al, 2008). This rapidly leads to formation of Atg11-containing autophagosomal structures at the mitochondrial surface, and these structures are instrumental for selective removal of complex I and complex III subunits (Timón-Gómez, Sanfeliu-Redondo, Pascual-Ahuir, & Proft, 2018). This is reminiscent of the mitochondria-derived vesicles (MDV) mechanism, which in mammals is responsible for local mitochondrial repair based on the mitochondrial export of 70 to 150 nm single- or double-membraned vesicles containing mitochondrial cargo that bud from the outer mitochondrial membrane, and which are subsequently degraded (Gustafsson & Dorn, 2019).…”
Section: Discussionmentioning
confidence: 99%